2016
DOI: 10.12669/pjms.326.10788
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of mothers on acute respiratory infection in children under five years

Abstract: Objective:To assess Knowledge, Attitude and Practices of mothers on ARI (Acute Respiratory Tract Infection) in children less than five years of age.Methods:This cross-sectional survey was conducted in the Department of Pediatrics, Darul Sehat hospital from 1st December 2014 to 28th February 2015. Mothers(n=335) who were local residents, had at least one child below the age of five years and coming to the hospital for any medical problem along with accompanying women were included. Foreign mothers and/or those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
27
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 10 publications
10
27
2
4
Order By: Relevance
“…This result shows that the majority of the mothers are not aware of the signs and symptoms of pneumonia, and thus this can be the reason why they do not bring their child early to the hospital for treatment. Whereas in other study majority of mothers were able to correctly pick signs and symptoms of pneumonia (16 ) Only 20% mothers indicated that keeping clean environment will prevent children from getting pneumonia whereas this result was much lower as compared to the study conducted in Pakistan on acute respiratory infection in children less than of five years, reported 81% (17).Few study has been found that Pneumonia is more associate with malnourished children (18).We further investigated awareness about vaccination as a preventive measure and only 19.2% of respondents recognized vaccination of pneumonia should be made compulsory for children. According to WHO report 2010 there is an extensive need for effective interventions program in all parts of the world in order to bring down mortality and morbidity rates due to pneumonia (19).…”
Section: Discussionmentioning
confidence: 71%
“…This result shows that the majority of the mothers are not aware of the signs and symptoms of pneumonia, and thus this can be the reason why they do not bring their child early to the hospital for treatment. Whereas in other study majority of mothers were able to correctly pick signs and symptoms of pneumonia (16 ) Only 20% mothers indicated that keeping clean environment will prevent children from getting pneumonia whereas this result was much lower as compared to the study conducted in Pakistan on acute respiratory infection in children less than of five years, reported 81% (17).Few study has been found that Pneumonia is more associate with malnourished children (18).We further investigated awareness about vaccination as a preventive measure and only 19.2% of respondents recognized vaccination of pneumonia should be made compulsory for children. According to WHO report 2010 there is an extensive need for effective interventions program in all parts of the world in order to bring down mortality and morbidity rates due to pneumonia (19).…”
Section: Discussionmentioning
confidence: 71%
“…Also, another study conducted in KSA showed that there was a deficiency in knowledge among mothers regarding the antibiotics, physician consultation and ARIs preventive measures (9) . Several worldwide studies showed that most of mothers asked for antibiotics for children with ARI as this misconception may be due to parents fear of severe illness thus thought antibiotic would help them to get better fast (8,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 99%
“…The excessive use of X-rays and laboratory investigations (5,6) are promoting factors in the spread of ARI. The assessment of parent's KAP Received great attention by many research workers (7)(8)(9) . Many parents use a potentially harmful herbals and remedies with wrong conceptions, also the lack of adequate knowledge about the correct method of applying antibiotics in the medical care of young children highlighted the importance of intensive research studies in the field of intensifying the use of proper preventive measures in dealing with ARI infected young children (10) .The objective of the study was to evaluate the KAP of Saudi mothers toward acute respiratory tract infection in children less than five years.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of government policies and programmes, establishment of anganwadis and PHCs, it is expected that people will seek care are by a physicians if their child is ill but in the present study only 67.61% of the participants believed in visiting a doctor for any complain and rest practised treatment at home which is unfortunate if compared to the work of Bham et al in Pakistan where 89% of the mothers sought care by a medical practitioner in case of any childhood illness. 7 In the present study about half of the participants were not aware of pneumonia. 32.38% of the mothers knew about the specific signs of pneumonia which is on similar lines to the study conducted by Ferdous et al in Bangladesh where 29% of mothers had prior understanding of signs and symptoms of pneumonia.…”
Section: Discussionmentioning
confidence: 57%